Issues in Methodology of Islamic Thought - IIIT - Cairo Office (International Institute of Islamic Thought, 1989)
During the period from Safar 9-12, 1410 H. / September 11-14,1989 A.D., a seminar on the "Issues in Methodology of Islamic Thought" was held at Amir AM al Qadir University of Islamic Studies (Qusantinah, Algeria). The seminar was organized by the university in conjunction with the International Institute of Islamic Thought (Washington, D.C.). A group of professors and students of both sexes from Amir Abd al Qadir University, as well as from the Central University, participated in the seminar activities. The opening session was attended by representatives from Qusantinah Province, the National Liberation Front, the Municipal Council, and the Religious Committee. Speeches were delivered by Dr. 'Ammar al Talibi, the University President and Chairman of the seminar; Dr. Gamal El-Din Attia, Academic Advisor of the International Institute of Islamic Thought and convenor of the seminar; and by Dr. Muhammad 'AM al Hadi Abu Ridah representing the guests of the seminar. The seminar included seven panels where twenty-one research papers, prepared for the seminar, were presented and discussed. These research papers covered the following topics: 1- Inference Methodology in the Qur'an: A Response to the Opponents of Faith, by Dr. Ahmad 'Atwah. 2- The Elements of Scientific Methodology in the Qur'an and al Sunnah, by Dr. Ghawi 'Inayah. 3 - Muslim Methodology in Islamic Theology, by Dr. Fawqiyah Husayn. 4 - The Methodology of Ideology in the Light of Contemporary Scientific Advances, by Dr. Muhammad Abd al Sattar Nassar. 5- An Overview of the Methodology of Recording History, by Dr. 'Abd al Halim 'Uways. 6- The Methodology of the Principles of Jurisprudence, by Dr. Abd al Hamid Madkur. 7- The Crises of Methodology in Modem Ideological Studies, by Dr. Muhammad Kamal al Din Imam. 8- The Scientific Methodology and Spirit of Ibn Khaldun and Its Relation to Islam, by Dr. 'Imad al Din Khalil ...